PENGARUH IMPLEMENTASI PROGRAM PELAYANAN KELUARGA BERENCANA (KB) TERHADAP PENINGKATAN KESEJAHTERAAN KELUARGA DI KECAMATAN MALALAYANG KOTA MANADO - RUKMANA, INDAH RIZKIA (ACTA DIURNA KOMUNIKASI, 2013)
Development of health policy and social welfare, among others, aimed at improving the quality of family planning programs. But in reality the implementation of family planning program is not maximized. Starting from these conditions, this study is intended to answer the question "whether the implementation of family planning programs affect family welfare". This study uses quantitative methods. The study was conducted by taking a sample of 5 (five) villages in the districts Malalayang. The research sample set of 50 underprivileged Household drawn at random every 10 sample villages Household. Collecting data using questionnaires and assisted with interviewing techniques. Statistical analysis of the data using linear regression analysis and product moment correlation. Processing the data using computer-assisted analysis SPSS version 12.0 for Windows. Based on the analysis of the data showed: (1) the regression coefficient implementation program for the welfare of family planning services is a scale 0.791 per unit. (2) the correlation coefficient implementation of family planning services to the welfare of the family is 0.863, while the coefficient of determination is 0.745 or 74.5%. Based on the results of that study concluded that the implementation of the family planning program and a significant positive effect on improving the welfare of the poor families. Based on these conclusions, it is recommended that the implementation of family planning program should be done better so it will be a major influence on the improvement of the welfare of the poor families. Keywords: program implementation, planning services, family welfare.